The Measurement of the Highest Vowel Pitch and Formant Using PRAAT Program - Ni Made Chandra Widayanti (Universitas Warmadewa, 2022)
This study is aimed to analyze the measurements of pitch and formant values in determining the highest vowels which derived from the voices of native and non-native. Linguistically, this research was related to the phonetics and phonology, by applying PRAAT application to calculate the frequency and formant of speech. The subject of the study in this research was vowels contained in several Indonesian words. The focuses were only the element of pitch and formant of the fourth respondents in uttering the vowel-contained words. The research method used in This study used the Forensic audio method. However, in this study, researchers only focus on identifying pitch and formants in the data to be analyzed. In addition, the data wa descriptive analysis with the presentation of data in the form of numerical tables and graphs.